(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
The teaching of English as a foreign language (EFL) has shifted from traditional teacher-centered approaches toward interactive, learner-centered methods. This article examines the effectiveness of modern interactive techniques such as digital tools, role-play, project-based learning, gamification, blended learning, and collaborative activities. Practical examples are provided to demonstrate how these strategies can improve learner motivation, communication, and critical thinking. By analyzing recent empirical studies, this article highlights how interactive approaches contribute to developing communicative competence and preparing students for real-life situations.